Heart Failure and Mortality in Patients With Nonvalvular Atrial Fibrillation Started on Novel Oral Anticoagulant Therapy: A Single-Center Experience - ÇİNÇİN, AHMET ALTUĞ; ATAŞ, HALİL; SÜNBÜL, MURAT (SAGE PUBLICATIONS INC, 2017)
Heart failure (HF) is the leading cause of in-hospital morbidity and mortality in the elderly population. Coexistence of HF and atrial fibrillation (AF) increases the risk of thromboembolic events. Oral anticoagulant therapy reduces the risk of thromboembolic events in patients with AF. Novel oral anticoagulants (NOACs) have been introduced as an alternative drug for prevention from thromboembolic events in patients with nonvalvular AF. The primary aim of this study is to investigate the clinical effects of warfarin, dabigatran, and rivaroxaban in patients with nonvalvular AF. The secondary aim of this study is to reveal the predictors of all-cause mortality in patients with nonvalvular AF undergoing NOACs therapy. The study population consisted of 171 patients with nonvalvular AF. Patients were divided into 3 groups according to the usage of oral anticoagulant therapy including coumadin (51 patients), dabigatran (52 patients), and rivaroxaban (68 patients). Although CHA2DS2-VASc score was similar between groups, HAS-BLED score was significantly higher in patients using rivaroxaban. Dyspepsia and itching were more common in patients using dabigatran. Heart failure and vascular disease were more common in the nonsurviving group (10 patients) than in the surviving group (110 patients) in patients using NOACs. Among age, sex, HF, hypertension, vascular disease, and CHA2DS2-VASc, which were included in the regression model, only the presence of HF was an independent predictor of all-cause mortality in patients using NOACs. In conclusion, the mortality rate is significantly higher in patients with HF using NOACs. Moreover, HF is an independent predictor of all-cause mortality in patients using NOACs.
Keywords: atrial fibrillation; heart failure; mortality; novel oral anticoagulants; ANTITHROMBOTIC THERAPY; WARFARIN; METAANALYSIS; DABIGATRAN; EFFICACY; ASPIRIN; SAFETY; STROKE; RISK; ASSOCIATION